Absolute trust in the goodness of the earth : new poems - Walker, Alice, 1944- (New York : Random House, 2003)
Presents more than eighty poems by African-American writer Alice Walker, covering such themes as grief, love, aging, acceptance, and the hectic pace of daily life.
Library Journal.
Publisher's Weekly.
Adult.
Adult
Keywords: American poetry